Simulasi Penelusuran Berkas Cahaya pada Lensa Tipis - Edi Wibowo, Catur (BERKALA FISIKA, 2008)
A program to simulated trace the beam of light have been done with Python programming language version 4.2. Program was simulated trace the beam of light in the convergen lens and divergen lens. Program was constuct by functions of canvas, create line, button and motion Â in object oriented programming Python. Object simulation is the convergen lens and divergen lens with focus 10 cm and hight of object 4 cm.The result of simulation is graphical user interface with mouse interaction. The trace of beam of light indicate that this simulation is according to theory.